L'educazione al paesaggio nell'ambito di un Osservatorio: conoscenza, consapevolezza, condivisione. L’esperienza del Canale di Brenta (Vicenza) - Castiglioni, Benedetta (Ri-Vista. Research for landscape architecture, 2015)
Starting from the approach proposed by the European Landscape Convention, which focuses on the role of people’s perceptions, aspirations and needs for increased awareness of landscape values, landscape education activities can be effectively implemented in the frame of the Landscape Observatories. The paper presents the experience of the Landscape Observatory of Canale di Brenta (Northeastern Italy), where in 2011-12 more than 1300 school children and their 80 teachers where involved in activities focused on knowledge, awareness and sharing of landscape and aimed to the reading of its complexity (denotative, connotative, interpretative and temporal reading) .